Refreshing course - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
With the growing complexity of the issues faced by CTA's partners, and the related key information-oriented tasks CTA has to undertake, there has grown, too, a need for the staff at the Centre's headquarters to be on top of these issues and their implicat